Penyuluhan Mencuci Tangan sebagai Upaya Mencegah Kecacingan di Panti Asuhan Assomadiyyah Tangerang - Makhabbah Jamilatun (Jurnal Pengabdian Pada Masyarakat, 2019)
EDUCATION OF HANDWASHING AS AN EFFORT TO PREVENT HELMINTHIASIS AT ASSOMADIYYAH ORPHANAGE TANGERANG. Children are the nation's assets in the future that should receive special attention, such as to protect them from various diseases and infections. Children have a habit of paying less attention to the need for handwashing in everyday life. Diseases that can be caused due to lack of their concern for handwashing, such as helminthiasis. One of the factors that result in high worm infection is the lack of handwashing. Based on this background, it is necessary to do community service, especially in children who are in orphanages in the hope of contributing to prepare early generation of health conscious, so that will have an impact on quality of students' character formation and care for health. The purpose community service activities are children in Assomadiyyah orphanages can understand the importance of hand washing and understand how to perform proper hand washing as well as its application in everyday life. Method of community service activities conducted by providing information and practices related to handwashing. The results of this community service activities is increasing understanding of the children at the Assomadiyyah orphanage about the importance of hand washing and can do it the right way.